(3LhGgQ GdcdeGJ aj GdYbhO hGdEjbGYGJs - (3GdUjQej, eadM Hf GdMSf Hf QTjO Hf UdGM, J (B873 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B....(3abO GdJeS efj HYV GdENhGf GdGYRI Ydi GdcQGe dOj Cf GLeY dg UjZ GdYbhO hGdEbGYGJ hCf CMQQgG dg aj hQjbGJ djfJbY HgG Ggd GdeYGedGJ hCdM Ydj aj Pdc ZGjI GdEdMGM hHGdZ aj GdWdH hGdGbJQGM (B...s
(3BNQgG (B:s
... (3hJJMag HeG MVQ ef WYGe hTQGH haGcgI hWjH COfGg TQH GdeGA Ch GdhVhA hUdGI QcYJjf YfOg hGdJCfjS HGdMOjK hGdJhOjY EPG NQL Je eG bUOfG EjQGOgs
(3JHUQI GdYfhGf (B:s
(3aj UjZ GdYbhO hGdEjbGYGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\281s
(3GdPQjYI (B5 - 199( 1307)s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis